2014
DOI: 10.2320/matertrans.ma201301
|View full text |Cite
|
Sign up to set email alerts
|

EBSD Analysis of Microstructure Evolution of Pure Iron Subjected to Sliding Wear and Related Change in Vickers Microhardness

Abstract: Sliding wear tests were carried on pure iron to investigate evolution of microstructure below worn surface. After the wear tests, grain boundary formation and lattice rotation were analyzed with electron backscatter diffraction (EBSD) method. In the vicinity of the worn surface, submicron grains separated by high-angle grain boundaries were generated. Below the submicron grain region, dominant microstructures were two kinds of low-angle grain boundaries which were horizontal and inclined to the worn surface, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The TEM observation in worn copper has shown that a matrix grain was significantly rotated below the fine-grained region 1) . Such lattice rotation below the fine-grained region was clearly manifested by the electron backscatter diffraction (EBSD) analyses in our previous study on pure iron 13) . The observed lattice rotation should be a…”
Section: Introductionmentioning
confidence: 67%
“…The TEM observation in worn copper has shown that a matrix grain was significantly rotated below the fine-grained region 1) . Such lattice rotation below the fine-grained region was clearly manifested by the electron backscatter diffraction (EBSD) analyses in our previous study on pure iron 13) . The observed lattice rotation should be a…”
Section: Introductionmentioning
confidence: 67%